2019
DOI: 10.1089/cbr.2018.2570
|View full text |Cite
|
Sign up to set email alerts
|

Combined Detection of HER2, Ki67, and GSTP1 Genes on the Diagnosis and Prognosis of Breast Cancer

Abstract: Objective: Breast cancer (BC) is a common malignant tumor in females. The combined assay of multiple molecular markers benefits the diagnosis and prognostic prediction. Human epidermal growth factor receptor 2 (HER2) facilitates the proliferation and differentiation of cancer cells through ligand binding. Ki67 is a tumor proliferation-related gene, whereas GSTP1 is a DNA repair-related gene. This study thus investigated the significance of HER2 and Ki67/GSTP1 gene combined assay in the diagnosis and prognosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“… 7 Another study has indicated that Ki-67 expression has a positive correlation with TNM stage and LNM, and a negative correlation with tissue grade and ER/PR expression. 7 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 7 Another study has indicated that Ki-67 expression has a positive correlation with TNM stage and LNM, and a negative correlation with tissue grade and ER/PR expression. 7 …”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our findings, HER2 expression has been revealed to positively correlates with tumor size, clinical TNM stage and LNM, while negatively correlates with ER/PR expression and tissue grade, implying that HER2 expression could be considered as a marker for breast cancer. 7 Another study has indicated that Ki-67 expression has a positive correlation with TNM stage and LNM, and a negative correlation with tissue grade and ER/PR expression. 7 Furthermore, we wanted to elucidate the relationships between ER, PR, HER-2 and Ki-67 expression and prognosis in breast cancer tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence has shown that the combination of several epigenetic biomarkers can improve the diagnostic accuracy for cancers. [ 53 , 54 ] It would be logical that a panel of epigenetic biomarkers, including PROM1, represents a potential diagnostic test for HNSCC. Future rigorous studies using larger sample sizes will be essential to validate this approach.…”
Section: Discussionmentioning
confidence: 99%
“…Methylation of HER2, Ki67, and GSTP1 are associated with BRCA TNM staging and tumor size and can be combined for early diagnosis and prognosis [19]. FECR1 circular RNA expression is coordinated by regulation of DNA methylation and demethylation.…”
Section: Introductionmentioning
confidence: 99%